Arterial hypertension in thyrotoxicosis: neuro3humoral regulation, hemodynamic and metabolic changes - P. Kh. Dzhanashija; G. B. Selivanova (Российский кардиологический журнал, 2004)
This review of literature, devoted to arterial hypertension in patients with thyrotoxicosis, describes the state of renin-angiotensin-aldosterone system, catecholamines and Cortisol metabolism, hemodynamic parameters. Pharmacologic correction of hemodynamic abnormalities and lipid metabolism changes is discussed. The information presented supports the conclusion that further study of the problem is necessary. The objective is to investigate neuro-humoral activation and metabolic changes, according to BP increase stage, thyrotoxicosis severity, BP dynamics during thyroid function compensation, and to optimise antihypertensive therapy in such patients.